Graphitic carbon nitride decorated with FeNi3 nanoparticles for flexible planar micro-supercapacitor with ultrahigh energy density and quantum storage capacity. Issue 32 (22nd July 2019) - Talukdar, Meenakshi; Behera, Sushant Kumar; Deb, Pritam
Abstract : Schematic description of graphitic-C3 N4 @FeNi3 (pseudocapacitive FeNi3 and electrochemical double layer g-C3 N4 ) heterostructure having energy density and quantum storage capacity for in-plane micro-supercapacitor application. Abstract : Portable miniaturized energy storage micro-supercapacitors have attracted significant attention due to their power source and energy storage capacity, replacing batteries in ultra-small electronic devices. Fabrication with porous and 2D graphitic nanomaterials with high conductivity and surface area leads to high-performance micro-supercapacitors. In order to satisfy the fast-growing energy demands for the next generation, we report performance and design of a 2D heterostructured EDLC (g-C3 N4 ) and pseudocapacitor (FeNi3 ) resulting in short ionic diffusion path and prominent charge storage based on synergic functionalities. This heterostructure system shows an enhanced quantum capacitance (38% enhancement) due to delocalized states near the Fermi level. Having achieved an areal capacitance of 19.21 mF cm −2, capacitive retention (94%), enhanced power density (17-fold), having ultrahigh energy density of 0.30 W h cm −3 and stability of the material even without any obvious degradation after 1000 cycles, this smart heterostructure acts as a new platform for designing high-performance in-plane micro-supercapacitors.